An Ancient Practice but a New Paradigm: Personal Choice for the Age to Spay or Neuter a Dog - Hart, Lynette A.; Hart, Benjamin L. (Frontiers in Veterinary Science, 2021)
Extensive practice and knowledge of the methods and effects of castration of male livestock and even humans has been widespread since ancient times, but only a few decades ago did neutering (including spaying) become a routine part of canine husbandry. In the US, the 6-month neuter became standard practice. Only recently, however, have some of the consequences of this major physiological alteration become evident. As the data-based study on 35 breeds reveals, there are major breed differences associated with effects of neutering, especially with early neutering, including increased risks of joint disorders and some cancers. The study of mixed-breed dogs reveals that the risk of joint disorders is increased in the large dogs. Implications of breed-specific and sex-specific effects for age of neutering have prompted the consideration of a new paradigm with regard to this practice. This involves focusing on each individual dog when deciding upon the appropriate age of neutering to avoid increasing the risk of a joint disorder or cancer above that inherent for the breed. For many breeds, particularly the smaller dogs, no effects were found for the age of neutering on joint disorders and the cancers followed. In these cases, the caregiver has a wide range of choice for neutering without increasing the dog’s risk for these diseases. In the future, additional research may reveal more about other increased risks for age-related cognitive dysfunction or elevated levels of luteinizing hormone caused by gonad removal, and lead to revised guidelines.